Cancer incidence and mortality around the Pan Britannica Industries pesticide factory, Waltham Abbey. Issue 2 (February 1997) - Wilkinson, P; Thakrar, B; Shaddick, G; Stevenson, S; Pattenden, S; Landon, M; Grundy, C; Elliott, P
Abstract : OBJECTIVES: To examine the incidence and mortality of cancer near the Pan Britannica Industries factory, Waltham Abbey, after reports of a possible cluster of all cancers and brain cancer in the vicinity. METHOD: Small area study of cancer incidence 1977-89, and mortality 1981-92, within a 7.5 km radius of the factory site. Postcoded cancer registrations and deaths in the study area were extracted from national data sets held by the Small Area Health Statistics Unit and compared with expected numbers computed by applying national rates stratified for age, sex, and deprivation to the local population (1981 and 1991 censuses). Observed/ expected (O/E) ratios were examined from 0-1 km and 0-7.5 km of the plant, and tests applied for a decline in relative risk with distance up to 7.5 km. RESULTS: There were 12, 859 incidence cancers (1977-89) from 0-7.5 km (O/E ratio 1.04; 95% confidence interval (95% CI) 1.02 to 1.06) and 385 from 0-1 km (O/E 1.10; 1.00 to 1.22). There was an excess of skin melanoma from 0-1 km based on 11 cases (O/E 2.13; 1.06 to 3.80), and an excess from 0-7.5 km of cancer of the lung, stomach and pancreas combined, and prostate (O/Es ranged from 1.09 to 1.13). Only the findings from lung cancer were suggestive of a decline in risk with distance, especially in the later period (1982-9). There were 9196 cancer deaths (1981-92) from 0-7.5 km (O/E 1.04; 95% CI 1.02 to 1.06) and 308 from 0-1 km (O/E 1.24; 1.11 to 1.39); and 25507 non-cancer deaths (O/E 1.02; 1.01 to 1.04) from 0-7.5 km and 745 (O/E 1.14; 1.06 to 1.22) from 0-1 km. There was evidence of a decline in mortality with distance for all cancers combined, lung cancer (P = 0.001 for each), and colorectal cancer (P < 0.05), and also for non-cancers (P = 0.001). Proportional mortality analyses suggested a decline in risk with distance for lung cancer (P = 0.003) but not for all cancers or the site specific cancers examined. There was no evidence of an excess in the incidence or mortality from brain cancer. For cancer mortality in the inner-most wards, the findings were, for the most part, well within the range of variation across the region as a whole. CONCLUSIONS: The study provides limited and inconsistent evidence for a localised excess of cancer in the vicinity of the PBI plant. At present, further investigation does not seem warranted other than continued surveillance of mortality and cancer incidence in the locality.